Pengaruh Brand Ambassador, e-WOM Quality dan Sender’s Expertise terhadap Purchase Intention: Studi Kasus pada New Honda BR-V N7X Edition di PT Honda Prospect Motor - Ayu Wulandari; Istiharini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Brand Ambassador, electronic Word of Mouth (e-WOM) quality, and sender’s expertise on consumer purchase intention toward the New Honda BR-V N7X Edition. A quantitative approach was employed using a survey method, with data collected from 99 respondents who were exposed to PT Honda Prospect Motor's digital marketing campaign. The results of multiple linear regression analysis indicate that all three independent variables simultaneously have a significant effect on consumer purchase intention, with sender’s expertise being the most dominant factor. These findings provide strategic implications for companies in optimizing influencer-based digital marketing strategies.